Adoption of Proprietary Online Exam Proctoring Software Using Multimedia Analytics System - Ayush Srivastava; Preeti Singh; Alka Singh (International Journal of Mobile Computing Technology, 2023)
This research focuses on the effects of online proctoring in facilitating the online test procedure for prospects, as well as how these tools affect engagement and learnability, as well as a retrospective investigation of other online examinations now in demand and a comparison of both. As a researcher, we learned that online proctoring is essential not only for a smooth examination process, but also for the cautious management of a student's career. This study was conducted as a result of the trends in the field of online examinations, which necessitates mentorship for students so that they remain aware of the importance of the knowledge they require for their careers and provide an honest exam. This is also the motivation for this study; for each student to perform well in exams, they must acquire knowledge; and for that, strict proctoring is necessary. As a result, it is reasonable to conclude that the capacity to efficiently proctor an online exam is a necessary feature for future scalability in the education and assessment fields. Human proctoring is also an expensive and time-consuming option. We offer a method that does automatic online proctoring without the need for human intervention in this research.
Keywords: COVID-19; Pandemic; Proprietary; examination; open-source; software